Caught in the act: how the U.S. lacey act can hamper the fight against cyanide fishing in tropical coral reefs - Calado, Ricardo (2014)
Cyanide fishing is one of the most destructive techniques employed to\ncollect live reef fish. While national laws of most source countries ban\nthis practice, cyanide is still widely employed to capture live reef\nfish for human consumption and marine aquariums. The United States is\none of the largest importers of live reef fish, and the implementation\nof new approaches to screen for fish caught with cyanide is urgently\nneeded. A fast and reliable noninvasive and nondestructive approach to\nscreen live reef fish for cyanide poisoning was recently developed, yet\ndeployment of this test may be obstructed by U.S. law. The Lacey Act\nprohibits the import, export, transport, and acquisition in interstate\nor international commerce of fish taken in violation of any foreign law.\nTherefore, if a fish tests positive for cyanide poisoning, the testers\ncould expose themselves to liability for potential Lacey Act violations,\nas they are knowingly engaging in an illegal act. To eliminate this\ndisincentive, the U.S. government should help conservationists develop\nprotocols on how to test for cyanide poisoning without violating the\nLacey Act.